ESIPT-active cinnamoyl pyrones are bright solid-state emitters: Revisited theoretical approach and experimental study. (March 2023) - Bremond, Emma; Boggio-Pasqua, Martial; Leygue, Nadine; Fodili, Mokhtar; Hoffmann, Pascal; Saffon-Merceron, Nathalie; Métivier, Rémi; Fery-Forgues, Suzanne
Abstract: Excited-state intramolecular proton transfer (ESIPT) is a photophysical process that may lead to superior emission properties. For a long time, cinnamoyl pyrone (CP) derivatives have been classified as non-ESIPT molecules. With the exception of those bearing a strong electron-donor substituent, they have been considered to have no interest from a spectroscopic point of view, because they are virtually not fluorescent in solution. Revisiting their photophysical behaviour in solution shows the complexity of the mechanisms involved. It appeared that CPs with no or weak electron-donor substituents indeed undergo ESIPT, but the facile access to a conical intersection subsequently induces non-radiative deactivation, hence the extinction of fluorescence in solution. When substituted by an electron-donating diethylamino group, the molecules deactivate through a radiative intramolecular charge transfer (ICT) state following an ESIPT process. In the solid state, the restricted access to conical intersection (RACI) makes most of the CP derivatives strongly fluorescent. Whatever the electron-donating strength of their substituent, most of these molecules become good emitters in the solid state, with emission ranging from turquoise blue to deep red. Although they need extensive purification, their one-step synthesis and spectacular aggregation-induced emission (AIE) properties make these molecules good candidates for applications in the field of AIE-probes and photoluminescent materials. Graphical abstract: Image 1 Highlights: All cinnamoyl pyrones undergo ESIPT as the first photophysical process. Then, according to substitution, various deactivation processes occur in solution. The restricted access to conical intersection induces strong emission in the solid state. These easily-synthesized compounds exhibit spectacular AIE effect.